The Mengoptimalkan Kepuasan Pelanggan: Dampak Kualitas Pelayanan dan Harga - Ghozali, Ghozali; Cahyaning Pratiwi, Elok; Ridha, Mukhammad (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
The aim of this study for investigate How quality service and price influence level satisfaction consumer. Quality service refers to how much Good something company give service to the customer, temporary price covers aspect price product or services offered. This study use study quantitative. Subject This study is UD Indah Jaya consumers. Data collection techniques include: questionnaire. Research result show exists strong relationship between Quality Factors Service and Price Factors towards Satisfaction Consumer. This is indicated by the value coefficient correlation high multiple. Coefficient value determination multiple show that part big Satisfaction Consumer influenced by both factor that, temporary part small influenced by other outside factors study. Findings from This study will give useful insight for company for optimize their strategy in increase satisfaction consumers, fine through enhancement quality service as well as determining strategies more price effective.